Planning The Layout of Production Facilities (Case Study of Diera Mutiara Internasional in Yogyakarta) - Trisolvena, Nana (Greenation Research & Yayasan Global Resarch National, 2023)
The layout of production facilities is one of the important factors in a company because it has an impact on optimizing the efficiency of the production process. The greater the efficiency, the production process time will be faster and the idle time will be less. This research was conducted to find out what production facility layout was applied by Diera Mutiara International. The method used in this research is by analyzing the layout of production facilities applied by Diera in completing the skincare production process and whether it is efficient. The results obtained from this study state that Diera uses a qualitative flow measurement layout where the movement between departments aims to bring locations that have high displacement rates closer. The conclusion of this study shows that Diera Mutiara International have met BPOM standards in designing the layout of their facilities in a very small factory size.